PENGARUH CSR TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING - Siti Khodijah; Syamsul Huda (FKIP Unswagati, 2023)
This study aims to determine the effect of Corporate Social Responsibility (CSR) on company financial performance as proxied by Return On Assets, Return On Equity, and Net Profit Margin moderated by company size partially in mining sector companies listed on the Indonesia Stock Exchange.The research population includes all mining sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample in this study was determined by purposive sampling method. The data analysis technique in this research is descriptive and verification. Hypothesis testing uses the Structural Equation Modeling Partial Least Square (SEM-PLS) analysis model. The results of the study show that (1) Corporate Social Responsibility has a positive and significant effect on Return On Assets. (2) Corporate Social Responsibility has no effect on Return On Equity. (3) Corporate Social Responsibility has a positive and significant effect on Net Profit Margin. (4) Company size weakens the effect of the relationship between Corporate Social Responsibility on Return On Assets. (5) Company size weakens the effect of the relationship between Corporate Social Responsibility on Return On Equity. (6) This is indicated by the p-value of Net Profit Margin.